Delayed injury of hippocampal interneurons after neonatal hypoxia‐ischemia and therapeutic hypothermia in a murine model. Issue 8 (11th September 2018) - Chavez‐Valdez, Raul; Emerson, Paul; Goffigan‐Holmes, Janasha; Kirkwood, Alfredo; Martin, Lee J.; Northington, Frances J.
Abstract: Delayed hippocampal injury and memory impairments follow neonatal hypoxia‐ischemia (HI) despite the use of therapeutic hypothermia (TH). Death of hippocampal pyramidal cells occurs acutely after HI, but characterization of delayed cell death and injury of interneurons (INs) is unknown. We hypothesize that injury of INs after HI is: (i) asynchronous to that of pyramidal cells, (ii) independent of injury severity, and (iii) unresponsive to TH. HI was induced in C57BL6 mice at p10 with unilateral right carotid ligation and 45 min of hypoxia (FiO2 = 0.08). Mice were randomized to normothermia (36 °C, NT) or TH (31 °C) for 4 hr after HI and anesthesia‐exposed shams were use as controls. Brains were studied at 24 hr (p11) or 8 days (p18) after HI. Vglut1, GAD65/67, PSD95, parvalbumin (PV) and calbindin‐1 (Calb1) were measured. Cell death was assessed using cresyl violet staining and TUNEL assay. Hippocampal atrophy and astroglyosis at p18 were used to assess injury severity and to correlate with number of PV + INs. VGlut1 level decreased by 30% at 24 hr after HI, while GAD65/67 level decreased by ∼50% in forebrain 8 days after HI, a decrease localized in CA1 and CA3. PSD95 levels decreased in forebrain by 65% at 24 hr after HI and remained low 8 days after HI. PV + INs increased in numbers (per mm 2 ) and branching between p11 and p18 in sham mice but not in NT and TH mice, resulting in 21–52% fewer PV + INs in injured mice at p18. Calb1 protein and mRNA were also reduced in HI injured mice at p18. At p18, somatodendritic attrition of INs was evident in all injured mice without evidence of cell death. Neither hippocampal atrophy nor astroglyosis correlated with the number of PV + INs at p18. Thus, HI exposure has long lasting effects in the hippocampus impairing the development of the GABAergic system with only partial protection by TH independent of the degree of hippocampal injury. © 2018 Wiley Periodicals, Inc.